2022
DOI: 10.1186/s12905-022-01693-2
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity among midlife women in India: well-being beyond reproductive age

Abstract: Background Currently, inequality in life expectancy across gender makes women outlive men. Adult women transit towards menopause around midlife accompanied by a series of natural physiological changes leading to several conditions such as osteoporosis, depression, and urinary incontinence, which puts them at a higher risk of having multimorbidity. Multimorbidity is often associated with poorer quality of life, leading to deteriorated work productivity and associated economic loss in midlife. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…However, our findings are on the contrary with the results of a community based study conducted among women aged 60 years and above who reported the prevalence of urinary incontinence to be around 16% and 23% among urban and rural residents (21). Nonetheless, evidence suggests urinary incontinencedeteriorates the quality of life among women (22). We observed incontinence to be associated with tobacco use which is consistent with the findings of a facility based study conducted among Indian women (23).…”
Section: Discussionsupporting
confidence: 80%
“…However, our findings are on the contrary with the results of a community based study conducted among women aged 60 years and above who reported the prevalence of urinary incontinence to be around 16% and 23% among urban and rural residents (21). Nonetheless, evidence suggests urinary incontinencedeteriorates the quality of life among women (22). We observed incontinence to be associated with tobacco use which is consistent with the findings of a facility based study conducted among Indian women (23).…”
Section: Discussionsupporting
confidence: 80%
“…We used 16 chronic conditions to assess multimorbidity which is another strength of this study, but these conditions were self-reported which might undermine the true population estimates. Evidence suggests self-reported conditions leads to misclassification bias which under-represents the issue being studied ( 37 , 38 ). However, previous studies have also suggested a high agreement between self-reported conditions and clinical assessed conditions ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The burden of multimorbidity in India is rapidly increasing due to increased longevity and exposure to chronic disease risk factors [ 10 , 11 ]. However, there is a lack of data on the prevalence and impact of complex multimorbidity in India.…”
Section: Introductionmentioning
confidence: 99%